PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, RISIKO BISNIS TERHADAP NILAI PERUSAHAAN SEKTOR KIMIA YANG DI INDONESIA - Chani Dinayu; Devi ana Sinaga; D. Sakuntala (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2020)
This study aims to determine the financial ratios represented by capital structure (DER), company size (ln total assets), business risk (DOL) to firm value. Data collection techniques using purposive sampling and obtained as many as 17 sample companies from 73 populations of chemical sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The analysis model uses multiple linear regression. Based on the results of the coefficient test, the R square value of 0.749 shows that the correlation or closeness of the relationship of capital structure, company size, business risk and company value is only 74.9%. Adjusted R Square value of 0.735 indicates that the variable capital structure, company size, and business risk explains the variable to the company value of 73.5%. In the F test shows that the value of Fcount> Ftable (53,644> 2.78) so that simultaneously DER, ln total assets, DOL affect the value of the company in the chemical sub-sector of 2014-2018. Whereas the T-test for Company Size is 0.00, which means it has a partial effect on Company Value. Based on these results it is recommended for investors to pay more attention to the value of DER, ln total assets, DOL before investing.